2D nanostructures: Potential in diagnosis and treatment of Alzheimer's disease - Tufail, Saba; Sherwani, Mohammad Asif; Shamin, Zahid; Abdullah,; Goh, Khang Wen; Alomary, Mohammad N.; Ansari, Mohammad Azam; Almosa, Abdulaziz Abdullah; Long, Chiau Ming *; Amar, Daud Iskandar Abdullah *; Khan, Farheen Badrealam; Al Menhali, Asma; et al. (Elsevier, 2024)
Two-dimensional (2D) nanomaterials have garnered enormous attention seemingly due to their unusual architecture and properties. Graphene and graphene oxide based 2D nanomaterials remained the most sought after for several years but the quest to design superior 2D nanomaterials which can find wider application gave rise to development of non-graphene 2D materials as well. Consequently, in addition to graphene based 2D nanomaterials, 2D nanostructures designed using macromolecules (such as DNAs, proteins, peptides and peptoids), transition metal dichalcogenides, transition-metal carbides and/or nitrides (MXene), black phosphorous, chitosan, hexagonal boron nitrides, and graphitic carbon nitride, and covalent organic frameworks have been developed. Interestingly, these 2D nanomaterials have found applications in diagnosis and treatment of various diseases including Alzheimer’s disease (AD). Although AD is one of the most debilitating neurodegenerative conditions across the globe; unfortunately, there remains a paucity of effective diagnostic and/or therapeutic intervention for it till date. In this scenario, nanomaterial-based biosensors, or therapeutics especially 2D nanostructures are emerging to be promising in this regard. This review summarizes the diagnostic and therapeutic platforms developed for AD using 2D nanostructures. Collectively, it is worth mentioning that these 2D nanomaterials would seemingly provide an alternative and intriguing platform for biomedical interventions.